math

let f(x)=3x-2 and g(x)= xsquared+6


then (f*g)(x)

  1. 👍 0
  2. 👎 0
  3. 👁 19
asked by ashley
  1. let f(x)=3x-2 and g(x)= xsquared+6

    f( g(x)) = 3(g(x)) - 2
    = 3 (x^2+6) -2
    = 3 x^2 + 18 - 2
    = 3 x^2 + 16

    1. 👍 0
    2. 👎 0
    posted by Damon

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra

    Solve for "x" in each equation. 1)xsquared+12x+25= 0 2)xsquared+4x-12= 0 3)xsquared-5x= 50 4)(x+1)squared= 169 5)2xsquared+5x= 12 6)(2x-5)squared= 225 7)x-4/x-3 = x+2/x+1 8)9/2x+1/3= 1/2 9)6/x-1= 3/x 10)2x/2x+2x= 4

    asked by Cute on October 9, 2013
  2. math(check my answers)

    SOLVE THE FOLLOWING EQAUTION BY COMPLETING THE SQUARE: 3. xsquared - 8x - 10 = 0 xsqaured -8x=10 xsquared-8x+(8/2)sqaured=10+(8/2)sqaured xsquared-8x+16=26 Answer: xsqaured-8x+16=26 WHAT DID I DO WRONG?

    asked by ki on April 9, 2013
  3. Algebra

    Solve for y in terms of x . Determine if y is a function of x . If it is, rewrite using notation and determine the domain. xsquared+12x-3y+9=0 is it xsquared + 12x +9=3y f(x)=xsquared + 12x + 6=y ?

    asked by Nicole on September 7, 2008
  4. algebra (parabolas)

    tell whether the graph opens upward or downward. then find the axis of symmetry and vertex of the graph of the function 1. y=xsquared-5 2. y=-2*xsquared+6x+7

    asked by Bri on March 20, 2011
  5. Math

    2a) Simplify the expressions for A and B, where A=x+4/xsquared+9x+20 and B= 3xsquared-9x/xsquared+3x-18 b) Are the two expressions equivalent? Justify your answer. c) Determine i) A-B ii) A•B iii) B÷A

    asked by Inder on August 3, 2016
  6. math

    1. 2xsquared-7x=-6 2. xsquared + 12x + 1= 0 3. xsquared + 6x + 20 = 0

    asked by robert on April 9, 2013
  7. Math

    The question is simply and answer in standard form 3x2(that is x squared)-2x+1+x2(xsquared)+2x-9 so I made it 3xsquared+xsquared=4xsaqured -2x+2x=0 the answer is: 4xsquared-(-8)=4xsquared+8 Then it asks the type of polynomial? I

    asked by B6 on November 12, 2012
  8. maths

    simplify xsquared-4x÷xsquared-2x-8

    asked by maso on September 16, 2015
  9. Math

    Using the quadratic formula solve xsquared=2/3x Using the quadratic formula solve xsquared=2/3x x^2 - 2x/3 = 0 x = [+2/3+/-sqrt(2/3^2 - 4(1)0)]/2

    asked by Veronica on July 6, 2007
  10. math

    xsquared + 8x- 10 =1

    asked by katy on April 9, 2013

More Similar Questions